Iron-catalyzed C(sp(2))-H alkylation of indolines and benzo[h]quinoline with unactivated alkyl chlorides through chelation assistance - Jagtap, Rahul A.; Samal, Pragnya Paramita; Vinod, C. P.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2020)
Regioselective C-H bond alkylation of indolines and benzo[h]quinoline with a wide range of unactivated and highly demanded primary and secondary alkyl chlorides is accomplished using a low-cost iron catalyst. This reaction tolerates diverse functionalities, such as C(sp(2))-Cl, fluoro, alkenyl, silyl, ether, thioether, pyrrolyl, and carbazolyl groups including cyclic and acyclic alkyls as well as alkyl-bearing fatty-alcohol and polycyclic-steroid moieties. The demonstrated iron-catalyzed protocol proceeded via either a five-membered or a six-membered metallacycle. Intriguingly, the C-7-alkylated indolines can be readily functionalized into free-NH indolines/indoles and tryptamine derivatives. A detailed mechanistic investigation highlights the participation of an active Fe(I) catalyst and the involvement of a halogen-atom transfer process via a single-electron-based mechanism. Deuterium labeling and kinetics analysis indicate that the C-H metalation of indoline is the probable turnover-limiting step. Overall, the experimental and theoretical studies supported an Fe(I)/Fe(III) pathway for the alkylation reaction comprising the two-step, one-electron oxidative addition of alkyl chloride.
Keywords: alkyl chlorides; Alkylation; C-H activation; chelation assistance; indolines; iron

An innovative light assisted production of acetic acid from CO2 and methanol: a first photocatalytic approach using a reusable cobalt(ii) molecular hybrid at atmospheric pressure - Saini, Sandhya; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Ray, Anjan; Jain, Suman L. (Green Chemistry, 2021)
Acetic acid is an important commodity chemical that is produced either by fermentation processes, or more commonly, through chemical routes such as methanol carbonylation with CO and H-2, acetaldehyde oxidation, or hydrocarbon oxidation. More recently, methanol hydrocarboxylation with CO2 and H-2 under thermal catalytic conditions has attracted interest. The synthesis of acetic acid from easily available CO2 is of great significance yet rarely reported. The present paper describes the first photocatalytic approach for the synthesis of acetic acid from methanol and CO2 under ambient reaction conditions without using molecular hydrogen. The maximum conversion of methanol achieved is 60% with a selectivity of 81% towards acetic acid using an octa-sulfur bound cobalt phthalocyanine (CoPc/S8) photocatalyst without an additional sacrificial electron donor. Product analysis, controlled experiments and DFT calculations suggest the formation of methylene carbene as a reactive intermediate. The developed methodology represents a potentially exciting approach for synthesizing acetic acid utilizing CO2 in a sustainable manner.

Iron-catalyzed regioselective C-H alkylation of indoles: an additive-free approach in renewable solvent - Pradhan, Chandini; Jagtap, Rahul A.; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Punji, Benudhar (Green Chemistry, 2023)
Alkylated indoles are important motifs in various biologically active molecules and drug candidates. Herein, we report a mild and efficient iron-catalyzed protocol for synthesizing alkylated indoles via C-H bond alkylation of indoles with unactivated alkenes, demonstrating a high level of regioselectivity. The reaction occurs under additive-free, solvent-free (or trace green solvent, 2-MeTHF) and less energy-intensive conditions using a sustainable metal catalyst and provides easy access to privileged alkylated indoles with anti-Markovnikov selectivity. Alkylation is compatible with important functionalities, such as fluoro, chloro, trifluoromethyl, alkenyl, ether, thioether, silyl, and siloxane, including heteroaryl, pyridinyl, carbazolyl, and indolyl moieties (45 examples, up to 96% yield). The developed protocol is very simple, straightforward, and fully accords with the principles of green chemistry. A detailed mechanistic investigation manifests the facile indole's C-H activation at the Fe(0) center, reversible 1,2-insertion of the alkene into the Fe-H bond of a metallacycle, and a turnover-limiting reductive elimination. Alkylated indoles are important motifs in various biologically active molecules and drug candidates.
Keywords: Aromatic Ketones; Green; organic synthesis

Indazole-5-amine (AIA) as competing corrosion coating to Benzotriazole (BTAH) at the interface of Cu: A DFT and BOMD case study - Samal, Pragnya Paramita; Singh, Chandrodai Pratap; Tiwari, Shivani; Shah, Vaishali; Krishnamurty, Sailaja (Computational and Theoretical Chemistry, 2024)
This study compares three organic compounds-benzotriazole (BTAH), imidazole (IM), and indazole-5-amine (AIA)-as corrosion inhibitors for copper substrates. Using Density Functional Theory (DFT) and Born-Oppenheimer Molecular Dynamics (BOMD) calculations, it identifies AIA as a promising and cost-effective alternative to the toxic BTAH. The adsorption strength on Cu(1 0 0) surfaces is ranked AIA>BTAH>IM for both neutral and deprotonated forms. These findings are supported by electronic parameter studies, including Bader charge analysis, density of states (DOS), charge density differences (CDD), and frontier molecular orbital analysis. AIA shows the best adsorption in a parallel orientation at the top site. Packing studies reveal that hydrogen bonding stabilizes the interaction energies within self-assembled AIA aggregates. Organometallic complexation studies reveal that deprotonated BTAH exhibits higher interaction energy with a single Cu atom compared to AIA when bonded through the carbon end, consistent with the findings from BOMD studies. However, on periodic Cu surfaces, AIA outperforms BTAH molecules as seen from adsorption energies. This investigation highlights AIA's potential as a superior and more economical corrosion inhibitor for copper.
Keywords: Adsorption; Born-Oppenheimer molecular dynamics; Corrosion inhibition; Density functional theory; Indazole derivatives

Iron-catalyzed C-C and C-N bond-forming tandem amidation offering access to 3-amino-3-aminomethyl-2-oxindole frameworks - Ankade, Shidheshwar B.; Pradhan, Chandini; Samal, Pragnya Paramita; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
An iron-catalyzed protocol for the synthesis of 3-amino-3-aminomethyl-2-oxindole heterocyclic structures is disclosed employing isatins and non-nucleophilic N-methoxybenzamides. This reaction class is associated with broad scope and tolerates numerous functionalities, such as fluoro, chloro, bromo, iodo, trifluoromethyl, nitrile, ester, ether, and alkenyl, including heteroaryl - thiophene, benzothiophene, carbazolyl, indolyl, eugenol, and polycyclic cholesterol moieties. Detailed mechanistic investigations reveal that the reaction proceeds via iron-catalyzed N-O bond cleavage in N-methoxybenzamides, generating formaldehyde and benzamide, and through the intermediacy of isatin-ketimines and N-(hydroxymethyl)benzamides. Overall, this amidation reaction involves one C-C and two C-N bond-forming tandem processes, providing a range of beta-amino-aminomethyl-oxindoles (45 examples) in up to 88% yields. image
Keywords: benzamide; iron; Isatin; tandem amidation; tetrasubstituted carbon stereocenter